(untitled) (Economics and region, 2020)
Current condition, problems and prospects for the domestic tourism industry development are studied. The main aspects hindering the tourism industry development in the country are considered and require further solutions. The current normative legal acts regulating issues in the field of tourism are considered and the attention is focused on the lack of correlation between the normative regulation of the branch and the share of revenues from the provision of tourist services in the country’s GDP. It is determined that further reorganization and development of tourism in our country is not possible without the active support and direct intervention of the state. The authors proposed the measures, the implementation of which will help harmonize national standards in the field of tourism and resorts with international standards and help improve the quality of the national tourism product. It is proved that the development of the tourism industry directly depends not only on strengthening state regulation of tourism at the national level, but also at the regional level, especially since the tourism management system at the regional and local levels in decentralization in Ukraine is far from perfect. Emphasis is placed on the need to implement EU legislation in the field of tourism and resorts, which contributes to the improvement of tourism legislation and developed recommendations for the implementation of mechanisms for tourism development in the country.